The Determinants of Self-Employment among Immigrant and Native-Born Workers in Canada - Huang, Minzhi (Université d'Ottawa | University of Ottawa, 2015)
Using 2011 National Household Survey data, this study examines how human capital and demographic factors influence self-employment decisions among native-born individuals and immigrants from different places of birth in Canada. The personal characteristics (age, gender, marital status, educational attainment and language ability) are crucial in explaining the self-employment decision. The results confirm that older age and marital status have positive impact on self-employment for both males and females. Moreover, the place of birth affects the incidence of being self-employment for both genders. Immigrants from Northern and Western Europe, Eastern Europe, West Central Asia and Other Eastern Asia show higher propensities to be self-employed than their Canadian-born counterparts. The rate of self-employment for other immigrants groups vary differently when the demographic and human capital variables are taken into consideration. This paper also examines the different impacts of determinants, such as level of education, geographical region and language proficiency on the self-employment choices of immigrants and native-born workers.